Conference of the Directors of the European Institutes of International Research in Mariánské Lázně (Czech Journal of International Relations, 1967)
By agreement and in cooperation with six other European institutes for the research of international relations, the Institute for International Politics and Economics (UMPE) in Prague invited the directors and leading representatives of institutes of this focus from almost all European countries to Czechoslovakia for a joint conference, the purpose of which would be to establish in scale of pan-European regular contacts between the main scientific centers of international relations research and at the same time to develop a suitable system of scientific cooperation in the study of problems of common interest, in a range of issues of European security and cooperation. The conference had to search for new forms of scientific cooperation also think about delineating topics for potential joint research projects.